The PARENTS AS LIFELONG LEARNERS FOR INDONESIA’S GOLDEN GENERATION 2045: A SYSTEMATIC REVIEW - Agus Saleh; Imat Maftuhah; Ukun Kurnia (Fakultas Agama Islam, Universitas Mathla'ul Anwar, 2025)
///The realization of Indonesia’s Golden Generation 2045 depends not only on formal education systems but also on the quality of learning environments within families. Parents play a strategic role as primary educators, role models, and facilitators of children’s development. However, rapid social change, digital transformation, and increasing educational demands require parents to continuously update their knowledge, skills, and parenting practices. This literature review examines parents as lifelong learners in shaping high-quality human resources toward Indonesia’s Golden Generation 2045. Drawing on international scholarly publications related to parental involvement, family learning, lifelong learning, and human capital development, the findings show that learning-oriented parents create supportive home learning environments, foster children’s cognitive and socio-emotional development, and strengthen character education. Positioning parents as lifelong learners is therefore a strategic approach to complement formal education and strengthen family-based education systems.